Pectin-bioactive glass self-gelling, injectable composites with high antibacterial activity. (1st February 2019) - Douglas, Timothy E.L.; Dziadek, Michal; Schietse, Josefien; Boone, Matthieu; Declercq, Heidi A.; Coenye, Tom; Vanhoorne, Valérie; Vervaet, Chris; Balcaen, Lieve; Buchweitz, Maria; Vanhaecke, Frank; Van Assche, Frederic; et al.
Graphical abstract: Highlights: Pectin-BG composite hydrogels were prepared by a relatively simple mixing technique. BG particles delivers Ca 2+ ions for internal pectin crosslinking. Composite hydrogels exhibited strong antibacterial activity against MRSA. Mineralization process of composite hydrogels occurred upon incubation in SBF. Composite hydrogels were cytocompatible with MC3T3-E1 osteoblastic cells. Abstract: The present work focuses on the development of novel injectable, self-gelling composite hydrogels based on two types of low esterified amidated pectins from citrus peels and apple pomace. Sol-gel-derived, calcium-rich bioactive glass (BG) fillers in a particle form are applied as delivery vehicles for the release of Ca 2+ ions to induce internal gelation of pectins. Composites were prepared by a relatively simple mixing technique, using 20% w/v BG particles of two different sizes (2.5 and <45 μm). Smaller particles accelerated pectin gelation slightly faster than bigger ones, which appears to result from the higher rate of Ca 2+ ion release. μCT showed inhomogeneous distribution of the BG particles within the hydrogels. All composite hydrogels exhibited strong antibacterial activity against methicilin-resistant Staphylococcus aureus . The mineralization process of pectin-BG composite hydrogels occurred upon incubation in simulated body fluid for 28 days. In vitro studies demonstrated cytocompatibility of composite hydrogels with MC3T3-E1 osteoblastic cells.